How can rural digital development activate agricultural land mobility? -Based on the dual perspectives of resource mismatch and labor mobility - Wang, Xingang (Frontiers in Environmental Science, 2025)
IntroductionAgricultural land transfer is crucial for achieving labor mobility and rational allocation of resources. The digital development of rural areas provides a new way to solve the dilemma of low level of agricultural land transfer in China.MethodThis article empirically tests the impact and mechanism of rural digital development on agricultural land transfer using a two-way fixed effects model and a mediation effects model, based on balanced panel data from 30 provinces in China from 2006 to 2023.ConclusionFirstly, the digital development of rural areas has significantly improved the transfer of agricultural land, and this impact is sustainable. After endogeneity and robustness tests, the results still hold true. Secondly, heterogeneity analysis found that the digital development of rural areas has a more significant impact on agricultural land transfer in central and western regions, the Yangtze River Economic Belt, provinces with lower levels of economic development and total factor productivity. Thirdly, mechanism analysis reveals that rural digital development improves agricultural land circulation by alleviating labor mismatch, land mismatch, and capital mismatch. At the same time, the digital development of rural areas has accelerated labor mobility and improved agricultural land transfer.DiscussionThe development of digital development in rural areas has a “latecomer advantage” and can balance regional imbalances. This article provides theoretical guidance for the relationship and future development between rural digital development and agricultural land transfer.